Reductive leaching of low-grade manganese oxide ores using pretreated straw as reductant. Issue 1 (2nd January 2021) - Sun, Yang; Fu, Gaofeng; Jiang, Lan
ABSTRACT: The extraction of manganese from a low-grade manganese oxide ore was investigated in the presence of pretreated straw as reductant in sulfuric acid medium. It was found that concentrated sulfuric acid disrupted the structure of cellulose, hemicellulose and lignin of straw, making it possible to hydrolyse into monosaccharide. The effects of stirring speed, reductant/ore mass ratio, sulfuric acid concentration, ore particle size, leaching temperature and leaching time were examined. The optimal leaching conditions were determined as: stirring speed of 300 rpm, reductant/ore mass ratio of 0.3, sulfuric acid concentration of 9% (v/v), particle size of 45–75 μm and temperature of 85°C for 180 min. Under the above conditions, 92.8% manganese and 10.8% iron were extracted. The experimental results indicated that a high manganese leaching efficiency was achieved with a relatively low iron extraction.